Characterization of graphene nanosheets obtained by a modified Hummer's method - Hack,Renata (2018)
ABSTRACT Natural graphite is an inexpensive and abundant source to obtain graphene nanosheets. The most efficient method for large-scale production is the chemical method, which is based on the oxidation of natural graphite. This paper reports the synthesis and characterization of graphene obtained by the Hummers method with some modifications. The results indicate a high degree of graphite oxidation, proving that the process was efficient. Analyses of field emission scanning electron microscopy (FEG), transmission electron microscopy (TEM), Raman spectroscopy, thermogravimetric analysis (TGA) and X-ray diffraction showed that the graphene produced presented characteristics similar to the commercial graphene.